Assessing Quality Quickly: Validation of the Responsive Interactions for Learning - Educator (RIFL-Ed.) Measure. Issue 6 (18th August 2022) - Sokolovic, Nina; Brunsek, Ashley; Rodrigues, Michelle; Borairi, Sahar; Jenkins, Jennifer M.; Perlman, Michal
ABSTRACT: Research Findings: In this study, we tested whether it is possible to reliably evaluate the quality of interactions between early childhood educators and children using a thin-slice coding approach. Ninety-seven early childhood educators were videotaped for two five-minute intervals: one mealtime observation and one standardized activity. Videos were scored using the shortened and revised 15-item Responsive Interactions for Learning – Educator (RIFL-Ed.) measure, an open-access measure that takes less than ten minutes to administer and score. The RIFL-Ed. demonstrated good psychometric properties when used for mealtime observations and scores were associated with the Emotional and Behavioural Support (b = 0.19, p = .02) – and to some extent the Engaged Support for Learning (b = 0.15, p = 0.07) – domains of the widely used Classroom Assessment Scoring System (CLASS): Toddler Version. Less than half of the variance in scores was shared across educators in the same classrooms. Practice or Policy: If these preliminary results can be confirmed in larger studies, the RIFL-Ed.—an open-access measure for which fast and free online training is available– can be used to affordably scale-up targeted quality assessment and improvement efforts in early childhood education and care settings, efforts which have been shown to positively impact children's developmental outcomes.